Pengaruh harga dan promosi terhadap keputusan pembelian sepeda motor honda beat pada CV. Prima Motor Pasirpangaraian (Studi Kasus Masyarakat Desa Rambah Jaya Kabupaten Rokan Hulu) - Juni Wahyu Fauzi; Rosmayani Rosmayani (Pelantar Press, 2022)
The research was conducted using two variables, where variable X was product innovation and variable Y was buying interest. The phenomena raised include Sedap Talent's efforts to innovate products by processing catfish into various kinds of products without preservatives, Sedap Bakat also already has a P-IRT business license, LP-POM MUI halal certificate and P-IRT Health Office certificate so that the product is safe for consumption. consumed, the distribution channels offered by Sedap Talent vary so that consumers can choose the distribution channel they want. The purpose of this study was to determine the effect of product innovation variables on purchasing decision variables in the Sedap Bakat business in Simpang Tiga Village, Bukit Raya District, Pekanbaru City. This type of research is descriptive with quantitative methods. The research location is at Jalan Gading Marpoyan Gang Ludang Noomor 130 RT 05 RW 08 Simpang Tiga Village, Bukit Raya District, Pekanbaru City. The sampling technique used incidental technique with a total sample of 50 respondents. The types and sources of data used in this study were obtained through observation, interviews, questionnaires and documentation. Then the data analysis techniques used in this study are Validity Test, Reliability Test, T Test, Coefficient of Determination, Hypotheses, statistics and simple linear regression using SPSS 22. For the results of the tests carried out, the results show that product innovation variables affect purchasing decisions in businesses. Tasty Talent in Simpang Tiga Village, Bukit Raya District, Pekanbaru City by 60% and 40% is influenced by other variables.